Augmented Fluoroscopy: A New and Novel Navigation Platform for Peripheral Bronchoscopy. Issue 2 (April 2021) - Cicenia, Joseph; Bhadra, Krish; Sethi, Sonali; Nader, Daniel A.; Whitten, Patrick; Hogarth, Douglas Kyle
Abstract : Background: The diagnosis of lung nodules continues to be a challenge. Confirmed diagnosis allows appropriate treatment for cancers and allows avoidance of more invasive procedures for proven noncancers. Currently, available lung biopsy technologies each have their own limitations, which affect the ability to successfully navigate to a suspicious nodule and to collect a diagnostic sample. Additional advancements in endobronchial navigation, localization, and guided biopsy are needed to obtain higher rates of definitive diagnosis for lung nodules. Methods: This is a prospective, multicenter study that assessed the localization success rate and diagnostic yield of bronchoscopies guided only by the LungVision platform. Physicians navigated to pulmonary nodules according to a proposed pathway and verified nodule location using radial endobronchial ultrasound before the biopsy. Results: Fifty-five patients were enrolled in the study. Two patients had >1 nodule that was evaluated on the day of the procedure. During bronchoscopy, the nodule localization success rate was 93%. The overall diagnostic yield measured the day of the procedure, based on the immediate rapid on-site pathology report, was 75.4%. Conclusion: LungVision provides reliable navigation and ability to biopsy pulmonary nodules with an acceptable success rate. The platform demonstrates a high localization rate of pulmonary nodules.